Religia obywatelska i etyka protestancka w dobie prezydentury George'a W. Busha - Modzelewski, Bartosz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
The presidency of George W. Bush was full of events that justify the question about the influence of religion for politics. This problem is particularly interesting because it concerns a multicultural American society that is associated with many denominations. At the same time, attention should be paid to the developing civil religion, which is a type of binder cementing social bonds. The author of this article, presenting selected political decisions, social facts and scientific theories, polemicizes with the thesis about the decisive influence of Protestant ethics on the White House. At the same time, he emphasizes the danger associated with such an approach to civil religion, which actually becomes a belief in American messianism.
Keywords: religion; civil religion; politics; the United States